Nahu Sanamang in the Tradition of Tulehu Indigenous People: A Study of Reciprocity in Maluku - Umarella , Samad (Journal of Ecohumanism, 2024)
This research explores the Nahu Sanamang tradition in Negeri Tulehu, Maluku, as a form of reciprocity in indigenous communities. Nahu Sanamang is a practice of gotong-royong that involves financial and social contributions to various celebrations, such as weddings, aqiqah, and other religious events. Through an ethnographic approach, this research reveals how this tradition functions in maintaining solidarity, identity, and social structure amidst changing times. Data were collected through interviews, participatory observation, and documentation. The results show that Nahu Sanamang plays a key role in maintaining communal and spiritual values in Negeri Tulehu, as well as helping Indigenous people face the challenges of modernization. The tradition reflects a form of balanced reciprocity that strengthens social cohesion and demonstrates cultural adaptation in the face of globalization dynamics.